RESPONSE OF YIELD AND QUALITY OF BROCCOLI TO TYPE OF NUTRIENT SOLUTION UNDER HYDROPONIC SYSTEM WITH MODIFIED NFT TECHNOLOGY - A. D. SALMAN; I. J. ABDUL RASOOL (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was carried out at the Dept. Hortic. and Land.Gard., Coll. Agric. Eng.Sci., University of Baghdad during fall season of 2019-2020, in order to evaluate the effect of nutrient solution type under hydroponic system (NFT) on growth, yield and quality of broccoli Brassica oleracea var.italica. Two experiments were carried out which were the standard solution experiment (Cooper) and the alternative solution experiment (ABEER) prepared from fertilizers. Results revealed that the type of solution used in the hydroponics system had non significant effect on the leaves content of N,K, Mg, Fe, Cu, B, Chlorophyll, leaves number, root length, weight of the main heads, number of side heads were not significantly affected. 13nt, reflected on the productivity under the nutrient solution (45.87 and 44.78 ton ha-1 for the standard and alternative solutions, respectively), While the effect of the alternative solution was recorded a significant increment for each of the leaves percent of phosphorous, manganese and zinc concentration, Number of days until harvest 50% of the plants (0.65%, 23.84,59.56 mg kg-1, 94.74 day respectively ),compared to the standard solution, which recorded a significant increment in the calcium percent in the leaves, plant height, leaves area, shoots dry weight, roots dry weight, shoots: roots dry weight, diameter of the main heads and weight of the side heads. As for the yield quality parameters, Results revealed the type of nutrient solution non significant effect on quality of broccoli. The results could be recommend the alternative solution (ABEER) as a promising nutrient solution in hydroponics system.